Correction: High efficiency of bamboo-like carbon nanotubes on functionalized graphite felt as electrode in vanadium redox flow battery. Issue 109 (10th November 2016) - Chang, Yu-Chung; Shih, Yu-Chen; Chen, Jian-Yu; Lin, Guan-Yi; Hsu, Ning-Yih; Chou, Yi-Sin; Wang, Chen-Hao
Abstract : Correction for 'High efficiency of bamboo-like carbon nanotubes on functionalized graphite felt as electrode in vanadium redox flow battery' by Yu-Chung Chang et al., RSC Adv., 2016, 6, 102068–102075.